Development and validation of a perceived abortion self-efficacy scale: results from Bolivia, Nepal and Nigeria - Kristen M Shellenberg; Valerie N Acre; Navaraj Bhattarai; Yinka Abiola Adojutelegan; Ayodeji Oginni (Sexual and Reproductive Health Matters)
The objective of this research was to develop and assess the validity of a scale to measure perceived abortion self-efficacy (PASE). Perceived abortion self-efficacy is defined as an individual’s perceived confidence in their ability to carry out the tasks necessary to end a pregnancy safely and successfully. During the first phase of this study between February and April 2018, we conducted qualitative research using in-depth interviews and focus group discussions with women in Bolivia, Nepal, and Nigeria to explore domains of PASE. Using the qualitative data, we prepared a draft set of measures with 31 items. In October and November 2018, the second phase of the study included field testing 31 draft items with a convenience sample of approximately 1200 women across the three study countries. Exploratory factor analysis was conducted to identify an appropriate scale structure, resulting in a 15-item, 3-factor model. The three factors represent the concepts of enlisting social resources, accessing information and care, and resilience. In the third and final phase in September and October 2019, the validity of the 15 scale items was assessed. The scale was administered to a new sample of approximately 400 women in each country. Confirmatory factor analyses were conducted to test model fit for the scale structure identified during the second phase. The results from this study suggest that the final PASE scale has considerable potential to be a valid measure of PASE. The new 15-item PASE scale presented in this paper can be used to evaluate programmes or interventions designed to improve women’s PASE and to assess the state of PASE in populations.